2015
DOI: 10.1002/pmic.201400315
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel targets of oncogenic EGF receptor signaling in lung cancer through global phosphoproteomics

Abstract: Mutations in the epidermal growth factor receptor (EGFR) kinase domain occur in 10-30% of lung adenocarcinoma and are associated with tyrosine kinase inhibitor (TKI) sensitivity. We sought to identify the immediate direct and indirect phosphorylation targets of mutant EGFRs in lung adenocarcinoma. We undertook SILAC strategy, phosphopeptide enrichment, and quantitative MS to identify dynamic changes of phosphorylation downstream of mutant EGFRs in lung adenocarcinoma cells harboring EGFR(L858R) and EGFR(L858R/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 60 publications
2
35
0
3
Order By: Relevance
“…The power of this approach was shown in 2007 by the identification of previously unknown ALK, ROS and PDGFRα activated NSCLC subtypes [7]. This research strategy has further matured and applied in the past years [8,[15][16][17][18][19].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The power of this approach was shown in 2007 by the identification of previously unknown ALK, ROS and PDGFRα activated NSCLC subtypes [7]. This research strategy has further matured and applied in the past years [8,[15][16][17][18][19].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…2,3 Studies have shown that aberrant activation of kinase signaling pathways contribute to abnormality in cellular processes which results in tumorigenesis. 4,5 Oncogenic activation of PI3K, Notch and hedgehog signaling pathways have been reported in HNSCC and they are being tested in clinical studies as potential targets. [6][7][8] Mass spectrometry-based proteome/phosphoproteome profiling has become a reliable method for studying the signaling pathways/events that are dysregulated in any given system.…”
Section: Introductionmentioning
confidence: 99%
“…Однако совместное использование 2-DG и ингибитора IGF1R значительно увеличивает смертность раковых клеток [50]. Во многих работах были показаны достоверные различия в профилях ПТМ для чувствительных и резистентных к противоопухолевым препаратам клеток, некоторые из этих ПТМ предлагается использовать в качестве маркеров для типирования опухолей и выбора подходящего лечения [51][52][53]. Две независимые группы исследователей продемонстрировали зависимость эффективности терапии глиобластомы ингибитором тирозинкиназ эрлотинибом от уровня фосфорилирования PKB/Akt (рис.…”
Section: птм и фармакотерапия ракаunclassified